Mejora del proceso de paneles de balsa en el área Ck de la Empresa Plantabal S.A. del cantón Quevedo, año 2014 - Coello Kutayton, Juan Carlos (2015)
This research aims to analysis for process improvement panels raft in the area of the company CK Plantabal SA Quevedo Canton, 2014 ".To know the reality of the company production data a month of each of the machines was taken and also of nonconforming material and product repair, knowing this fact became known to the directors of the company which was the neck bottle production, which gave the approval to invest in what is necessary to achieve better efficiency in machinery and plant personnel. For this survey were to know what he thought each employee and whether they knew the reality of the company.With the changes we were able to increase production by between 15 and 20% in all thicknesses. The amount of nonconforming product that was considerable, it was possible to reduce between 15 and 20%. The number of failures that caused loose modules was reduced by between 13 and 18%. Changes made to the primary and secondary oven has allowed the company to better their bottlenecks caused problems of different natures, so that production is much slower. He also managed to increase production in this area between 15 and 30%. In cost benefit it yielded 1.54. This means that for every dollar invested investors have a profit of $ 0.54 USD, and cost benefit analysis of the project was greater than 1 so that the project is profitable.